2021
DOI: 10.1051/e3sconf/202132204001
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characterization of African catfish smoked sausage with different liquid smoke concentrations and immersion durations

Abstract: Product diversification is needed to increase selling and marketing prices. One of them is the African catfish sausage product. Liquid smoke has been used commercially by the food industry. This study aimed to determine the physical and chemical properties of smoked African catfish after adding different concentrations of liquid smoke and immersion duration. The chemical analysis measured the levels of protein, fat, and phenol. The results showed that sausage with a concentration of 20% liquid and soaking for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…A significant amount of saturated fatty acids present in the fat added to all fish sausage samples contributed to the inhibition of lipid oxidation processes, which is consistent with the conclusions of S. You et al (2022). The low content of fat oxidation products in smoked sausages is also explained by the presence of antioxidants in the smoke, in particular phenols, which can inhibit the oxidation process (Abeyrathne et al, 2021;Ernawati et al, 2021) The degree of proteolysis and microbiological processes was studied by changes in the volatile basic nitrogen content (VBN). The nitrogen content of volatile bases increases during storage under the influence of enzymatic processes and the vital activity of microorganisms and is accompanied by the breakdown of amino acids to form ammonia, mono-, di-, and trimethylamines.…”
Section: Figure 2 Organoleptic Evaluation Of Fish Sausages During Sto...supporting
confidence: 84%
“…A significant amount of saturated fatty acids present in the fat added to all fish sausage samples contributed to the inhibition of lipid oxidation processes, which is consistent with the conclusions of S. You et al (2022). The low content of fat oxidation products in smoked sausages is also explained by the presence of antioxidants in the smoke, in particular phenols, which can inhibit the oxidation process (Abeyrathne et al, 2021;Ernawati et al, 2021) The degree of proteolysis and microbiological processes was studied by changes in the volatile basic nitrogen content (VBN). The nitrogen content of volatile bases increases during storage under the influence of enzymatic processes and the vital activity of microorganisms and is accompanied by the breakdown of amino acids to form ammonia, mono-, di-, and trimethylamines.…”
Section: Figure 2 Organoleptic Evaluation Of Fish Sausages During Sto...supporting
confidence: 84%
“…The amount of ash is not regulated by Ukrainian and international standards for fish sausages, so it is not possible to compare its content with any established regulations. However, ash is made up of minerals such as iron, zinc, and phosphorus, which are important for achieving a balanced diet Ernawati et al, 2021).…”
Section: Table 2 Chemical Composition Of Fish Sausagesmentioning
confidence: 99%
“…E. Ernawati et al (2021) highlighted the chemical composition of smoked African catfish sausages made using smoking liquid. It was found that depending on the concentration of liquid smoke and the duration of immersion, the protein content ranged from 42.96% to 43.88%, the fat content from 11.34% to 12.89%, and the average moisture content was 20%.…”
Section: Table 2 Chemical Composition Of Fish Sausagesmentioning
confidence: 99%
See 1 more Smart Citation